2012
DOI: 10.1155/2012/475202
|View full text |Cite|
|
Sign up to set email alerts
|

Desmoid Fibromatosis in Pediatric Patients: Management Based on a Retrospective Analysis of 59 Patients and a Review of the Literature

Abstract: Background. Only limited data are available concerning desmoid tumor in children. Methods. Fifty-nine children and adolescents with desmoid tumor treated in 2 French cancer centers with a very long followup were retrospectively reviewed. Results. Median age was 6 years (range, 0–15). Tumors mainly involved the limbs (42%). Five cases occurred in a context of genetic disorder. Surgery was first-line treatment in 80% of cases. Resection was microscopically complete in 3 patients (pts), with a microscopic residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
(64 reference statements)
3
33
0
Order By: Relevance
“…Therefore, surgery as the mainstay is under debate and a wait‐and‐see policy as initial strategy in a none‐life‐threatening site and in the absence of marked progression is being adopted. Furthermore, function‐sparing intervention should be preferred to aggressive surgery aiming at negative margins …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, surgery as the mainstay is under debate and a wait‐and‐see policy as initial strategy in a none‐life‐threatening site and in the absence of marked progression is being adopted. Furthermore, function‐sparing intervention should be preferred to aggressive surgery aiming at negative margins …”
Section: Discussionmentioning
confidence: 99%
“…Whether or not age has a prognostic impact is controversial . Two studies of the paediatric population showed that younger age (<10 years) was a favourable prognostic factor .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the twenty-four comparative studies, the patients in the control group were selected from the same hospital in which the study was performed. Four studies included patients with primary desmoid tumours 8,12,17,32 . Only one retrospective study compared the main clinical characteristics of the patients at baseline, showing no significant differences between the intervention groups 25 ; however, five studies conducted a multivariate analysis to control for potential confounders at baseline [9][10][11]17,22 .…”
Section: 22mentioning
confidence: 99%